Bringing mom and dad to college: The separate role of mothers and fathers in female undergraduates’ mental outlook - SMITH, C. Veronica (Institutional Knowledge at Singapore Management University, 2012)
Research shows that children are influenced by both parents but has ignored the study of complementary roles of parents in young adult development. We measured female undergraduates life-satisfaction, self-esteem, and autonomy, and their perceptions of their parents roles. Results showed that mothers and fathers have unique roles in adolescent development.